CFD ANALYSIS TO IMPROVEMENT THE USE OF WIND DIRECTORS ON BOX TRUCK FOR DRAG REDUCTION - Alfian, Shova (Barometer, 2023)
Aerodynamics is one of the factors that can increase the efficiency of fuel consumption. The smaller the drag coefficient, the more efficient the vehicle. The current condition is that there are still many uses/installations of wind guides without taking into account the functions and benefits and there is still no regulation that regulates in detail the use of wind guides. So it is necessary to do this research with the aim of knowing the benefits of using the right wind guide in order to reduce the value of the drag coefficient and it is hoped that this research can be applied in the use of a wind guide. This research was conducted using three types of models at the lowest speed of 20 km/hour and the highest speed of 80 km/hour. The simulation results on trucks with 40 cm lower wind guides, trucks with upper wind guides and trucks with full wind guides using ansys workbench software, show that full wind driven trucks have the smallest Cd value. There was a decrease in the value of the cd from the 40 cm lower wind-directed truck model to the full wind-directed truck model. However, to show more accurate results, it is necessary to conduct a road test and flow of fluid from four sides.